DroMPI: Parallel Computation Over Drop Computing - Grosu, George-Mircea; Nistor, Silvia-Elena; Ciobanu, Radu-Ioan; Dobre, Ciprian; Pop, Florin (2024 IEEE 24th International Symposium on Cluster, Cloud and Internet Computing Workshops (CCGridW), 2024)
With the advancement of technology and the spread of multi-core systems, the need for parallelization arises and the interest in programming models is growing. At the same time, new distributed computing models have been proposed, being in fierce competition to obtain the highest possible performance. The Drop Computing Paradigm proposes the idea of decentralized computing over ad-hoc opportunistic networks of mobile and Edge devices. In this respect, the Drop Computing model does not only aim to achieve a minimum turnaround time but also to optimize other characteristics related to mobile devices, such as limited resources and opportunistic communication. Therefore, it is necessary to define a new programming model called DroMPI that intends to extend the capabilities of current parallel and distributed programming models, based on the Drop Computing paradigm. Therefore, the solution aims to develop a library that takes advantage of hardware capabilities in the interest of the Drop Computing paradigm and also provides programmers with a high-level programming interface. The library's features will be based on the Message Passing Interface (MPI) standard, which will be responsible for inter-node parallelization. The name of the library, DroMPI, is an acronym for Drop Computing and MPI. The implementation of the model will be responsible for the management of communication between nodes and for providing an Application Programming Interface (API) for the development of parallel applications in the Drop Computing paradigm.